Análise do comportamento de blocos de concreto para pavimentação com adição de resíduos de construção e demolição - Pitol, Aline Paula (2014)
The civil construction is an impacting industry with respect to negligence against the unbridled exploitation of resources and dispose of them. The use of construction and demolition waste as aggregates for construction are an alternative for minimizing the impacts generated by the same. So, the objective of this study is to analyze the influence of the substitution of natural aggregates by recycled aggregates on the compressive strength of concrete block for paving. The concrete block paving were made at the Laboratory of Testing Technology, Federal University of Tecnology - Paraná campus Campo Mourao, in a vibro-press VIBRAÇO available on the same. Were produced blocks from the dash 1:4, with the substitution of 10 and 15% where it was found that the compressive strength for the substitution of 10% the resistance decreased 12,8%, to 15% substitution its decreased 26,4%, which results in a decrease of 12.6% for every 5% addition of waste from construction and demolition. This way, it`s possible to conclude that the replacement of natural aggregates by recycled aggregates is a possible alternative if higher substitutions and other tests are performed.